MORPHOSEMANTIC FEATURES OF MEMBUAT ‘MAKE’ IN THE LIGHT VERB CONSTRUCTIONS OF INDONESIAN - Danang Satria Nugraha (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
Light verb constructions (LVCs) are combinations of a verb and a noun that operate as a referee for a distinctive idiomatic-like meaning in which the noun is the central focus of meaning deduction. This study aimed to identify and describe Indonesian LVCs as morphosemantic phenomena. The dataset comprises Indonesian sentences containing featured LVCs. Three corpora were utilized as data sources: Leipzig Corpora Collection – Indonesian (LCCI), SEAlang Library Indonesian Text Corpus (SEAlang), and Kamus Besar Bahasa Indonesia (KBBI). In this study, a framework from Morphosemantics has been employed to provide the deep analysis technique. The results revealed the following two folds. First, at the morphological level, the Indonesian verb membuat 'make' is a clear indicator of the existence of LVCs. Second, on a semantic level, the verb membuat ‘make’ in Indonesian LVCs tends to produce ACTION type verbs, AGENT paired argument of verbs and RESULTATIVE grammatical meaning. This study suggested that further research be done on the morphosyntactic features of the Indonesian LVCs verb membuat 'make.'